Opportunistic top predators partition food resources in a tropical freshwater ecosystem. (14th June 2017) - Villamarín, Francisco; Jardine, Timothy D.; Bunn, Stuart E.; Marioni, Boris; Magnusson, William E.
Abstract: The structure of food webs may be strongly influenced by the distribution of top predators in space and time. The Amazon biome is the only region in the world where four alligatorid species are known to occur in sympatry, and they attain high densities in some regions. As top predators with a diverse range of prey species occupying different trophic levels, their impact upon food webs should be substantial, but the degree to which crocodilians differ in their food sources, and potentially avoid competitive exclusion where they occur syntopically is not well understood. Although most crocodilians are considered generalist opportunistic predators that feed on any source of protein available in the environment, Amazonian crocodilians show broad differences in the proportions of prey items they consume. It is believed that these differences may in part reflect habitat use, but it is unknown to what extent they represent interspecific differences in prey preferences or are a direct function of habitat selection. Stable carbon isotope data (δ 13 C) of crocodilians and their potential prey were used to assess differences in reliance on terrestrial versus aquatic resources. These data were then placed in a spatial context using classified maps that reflect habitat types (headwater streams, mid‐order flooded‐forest streams and várzea floodplains) to elucidate whether dietary differences are explained by habitat selection or are more likely a reflection of prey preferences. We found evidence for differences in types of basal resources supporting these crocodilians. Mean δ 13 C values were highest in Paleosuchus trigonatus (Schneider's dwarf caiman, −25.7 ± 1.2‰), intermediate in Caiman crocodilus (spectacled caiman, −27.4 ± 1.2‰) and Paleosuchus palpebrosus (Cuvier's dwarf caiman, −27.7 ± 1.1‰) and lowest in Melanosuchus niger (black caiman, −29.9 ± 1.3‰). A progressive decrease in δ 13 C values of crocodilian tissues occurred from headwaters to floodplains, which most likely reflects a progressive increase in autochthonous over allochthonous inputs in lower reaches of streams. The shift from terrestrial to aquatic resources sustaining these sympatric predators mirrors their spatial distribution along this ecotone. However, after taking into account the habitat in which pairs of syntopic individuals of distinct species occurred, significant differences in δ 13 C values suggest that P. trigonatus and P. palpebrosus have different prey bases. Thus, despite being opportunistic predators, our results show that differences in crocodilian diets likely result from prey preferences and not only from habitat selection. These findings suggest that some species of crocodilians may be less generalist than traditionally thought and their influence on terrestrial or aquatic food webs might be species specific.